If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(3t + -5) + 3t = 7t + -3 Reorder the terms: -2(-5 + 3t) + 3t = 7t + -3 (-5 * -2 + 3t * -2) + 3t = 7t + -3 (10 + -6t) + 3t = 7t + -3 Combine like terms: -6t + 3t = -3t 10 + -3t = 7t + -3 Reorder the terms: 10 + -3t = -3 + 7t Solving 10 + -3t = -3 + 7t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-7t' to each side of the equation. 10 + -3t + -7t = -3 + 7t + -7t Combine like terms: -3t + -7t = -10t 10 + -10t = -3 + 7t + -7t Combine like terms: 7t + -7t = 0 10 + -10t = -3 + 0 10 + -10t = -3 Add '-10' to each side of the equation. 10 + -10 + -10t = -3 + -10 Combine like terms: 10 + -10 = 0 0 + -10t = -3 + -10 -10t = -3 + -10 Combine like terms: -3 + -10 = -13 -10t = -13 Divide each side by '-10'. t = 1.3 Simplifying t = 1.3
| -2x+7=16 | | 4(x+1)+2x=x+8 | | 16v^2+40vg+25g^2= | | (2x-3)(6x+4)=4x(3x+5)+18 | | 5/6-(1/12x4) | | 5/6-1/12x4 | | V=6*4 | | 40x=30(2+x) | | 3.5/18=2.8/s | | x+5x=3x+6 | | 48(-5/6r) | | 5(x+4)=-(x-2) | | 100.48=3.14x^2*2x*8 | | x^4+8x^3-9x+9=0 | | 100.48=3.14x^2*2x | | 2(3)-3(9)=1.5 | | y-5=4/5(x-5) | | 7y-2=-(y-14) | | (3x+22)+(3x+22)=8x-23 | | 8s-20=-47+5s | | -6.9(x-2)-6.6(x-6.1)=21.66 | | 12abc^2+12a^2bc-6ab+3bc=0 | | 4t+5=2t+15 | | 5x-4-25=6-3x+2 | | 108s^2-75= | | 6n-14=-13+5n | | 4x+8(1-x)=16 | | 16/40=x^2 | | 4x+3y=1fory | | -¼(6-x)/1/2-1/6 | | 0.08(5)=0.05(5+x) | | f(x)=3x^2graph |